PENGARUH UKURAN PERUSAHAAN , RASIO UTANG, TINGKAT PERTUMBUHAN PERUSAHAAN TERHADAP PRAKTIK MANAJEMEN LABA - B41108112, Hendra (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2013)
The purpose of this research is to examine the effect of firm size,debt to equity ratio, and firm growth on earning management practice in sample companies. Discretionary accrual is used to proxy earning management based on Modified Jones Model. This research is an econometric research based on panel data. 16 companies from insurance company and securities company listed on Indonesia Stock Exchange (IDX) from 2008-2011 are selected as research samples by purposive sampling method. Total observations used in this research are 63 observations. Data are analyzed by multiple regressions method. According to t-test result, this research finds significant negative relationship between firm size and earning management. This research finds no significant relationship between debt to equity ratio and earning management. This research also finds no significant relationship between firm growth and earning management. R-squared result suggests that earning management can be explained by firm size, debt to equity ratio and firm growth. Keywords: Earning Management, Firm Size, Debt to Equity Ratio, Firm Growth